Intracellular Replication of Mycobacterium marinum within Dictyostelium discoideum: Efficient Replication in the Absence of Host Coronin - Solomon, Jonathan M. (American Society for Microbiology, 2003)
Mycobacterium marinum causes tuberculosis-like disease in fish and amphibians and has been used as a model mycobacterial species because of its rapid growth and less stringent containment requirements relative to other mycobacterial species. We demonstrate here that M. marinum grows within Dictyostelium discoideum cells, allowing the genetic analysis of host factors that may modulate the replication of mycobacterial species. Intracellular growth of M. marinum was shown to mimic the properties previously observed for growth within cultured phagocytes. A defined bacterial mutant defective for growth within phagocytic cells was shown to be similarly defective for growth within D. discoideum. To test the role of host coronin, which was previously hypothesized to positively modulate mycobacterial growth within mouse macrophages, a defined D. discoideum coronin mutant was analyzed. Surprisingly, the absence of coronin resulted in enhanced intracellular replication of M. marinum relative to the control wild-type strain. Consistent with previous observations, some phagosomes showed persistence of coronin about the surface of the compartment, but colocalization of the protein was far from uniform. We conclude that in D. discoideum factors other than coronin support intracellular replication of M. marinum.